Quaking Regulates Hnrnpa1 Expression through Its 3′ UTR in Oligodendrocyte Precursor Cells - Zearfoss, N. Ruth (Public Library of Science, 2011)
In mice, Quaking (Qk) is required for myelin formation; in humans, it has been associated with psychiatric disease. QK regulates the stability, subcellular localization, and alternative splicing of several myelin-related transcripts, yet little is known about how QK governs these activities. Here, we show that QK enhances Hnrnpa1 mRNA stability by binding a conserved 3′ UTR sequence with high affinity and specificity. A single nucleotide mutation in the binding site eliminates QK-dependent regulation, as does reduction of QK by RNAi. Analysis of exon expression across the transcriptome reveals that QK and hnRNP A1 regulate an overlapping subset of transcripts. Thus, a simple interpretation is that QK regulates a large set of oligodendrocyte precursor genes indirectly by increasing the intracellular concentration of hnRNP A1. Together, the data show that hnRNP A1 is an important QK target that contributes to its control of myelin gene expression.